Implementasi Profit And Loss Sharing (PLS) Pengrajin Kain Tenun Sutera di Kabupaten Wajo di Tinjau dari Konsep Ekonomi Islam - Syafruddin; Khalid; Suarni (Journal of Islamic Economic Scholar, 2023)
Finding out the profit and loss distribution system in the silk woven fabric sector in the Wajo district is the goal of this type of qualitative research. The author conducts fieldwork-based interviews and documentation to produce the processed data. According to the study's findings, Wajo district's silk weaving industry's attempt to introduce profit sharing was having trouble. When the profits are distributed fairly in accordance with the original agreement, but the losses are only borne by the craftsmen by deducting work wages if the thread is damaged, and the capital owner does not contribute to the distribution, Islamic economic principles are not applied. This goes against the tenets of Islamic economics, which hold that gains and losses should be distributed equally and should not be detrimental to any party.